The socio‐ecological psychology of residential mobility - Oishi, Shigehiro; Tsang, Shelly (Journal of Consumer Psychology, 2022)
AbstractFrom ancient time, Homo sapiens moved around in search of a better life. Although the development of agriculture and industrialization no longer necessitates frequently moving to find new food sources, people today still change their residences for a variety of reasons. This article highlights key findings from residential mobility, focusing on its implications for the self, social relationships, societies, and well‐being. Generally, residential mobility shifts individual attention away from collective attributes toward personal attributes. It also changes people's relationship styles and preferences, leading individuals to favor wider social networks, more open communication, low‐commitment groups, and egalitarian helpers. In addition, it increases tolerance for norm violations and moral deviations. Lastly, residential mobility can explain some cross‐national and within‐nation variations. This article reviews recent psychological research on residential mobility and then discusses limitations, paradoxical findings, and future directions.